DFTB investigations of the electronic and magnetic properties of fluorographene with vacancies and with adsorbed chemical groups - Sakhraoui, Taoufik; Karlický, František (Physical chemistry chemical physics, 2022)
The electronic and magnetic properties of fluorographene (CF) in the presence of F-vacancy defects and/or chemical groups (-OH, -CN, or -NH2) were computationally investigated within the framework of the density functional tight-binding (DFTB) method. The current method parameterization allowed us to perform accurate electronic structure calculations (at the ab initio level of many-body methods in the particular case of CF) for hundreds of atoms in the computational cell. We show that the F-vacancy and/or chemical groups influence the magnetic structure, which depends on the number of defects and their distribution between the two sides of the graphene plane. Interestingly, we pointed out a possibility of imprinting local magnetism not only via F-vacancy and -OH combinations, but also using F-vacancies and -CN or -NH2 groups. In such structures, the magnetic ordering and the total magnetic moments depend on their adsorption sites and their presence in the same or on opposite sides of the graphene plane. We devote particular attention to the interacting chemical group with the F-vacancies. The interaction between the adsorbed chemical group and the unpaired spins associated with the F-vacancies in CF gives rise to interesting magnetic structures. Finally, the zigzag-like direction is shown as the most preferred for the defluorination of CF. Stable ferrimagnetic zigzag chains with interesting properties are considered to be basic magnetic features in perturbed CF. Our work provides new guidelines for engineering multifunctional spintronic components using CF as a base material. We believe, in particular, that the magnetism is predominantly controlled by the F-vacancies, and the ferromagnet can ideally be regulated via the adsorption of a chemical group on a defective CF supercell.